The social function of the principle of insignificance and its applicability by the police authority - Gugelmin, Bruno Henrique; Nagorski, Carolina Dubena; da Silva , Rafael dos Santos; Pires , Débora Aparecida; Anton , Edgar; de Carvalho , Estefani; da Cruz, Luiz Gustavo; Karvat, Jaciel Santos (Seven Editora, 2023)
This scientific article aims to analyze the social function of the principle of insignificance and its applicability within the scope of the police authority. The principle of insignificance is a doctrinal and jurisprudential construction that seeks to exclude the typicality of behaviors that, despite formally qualifying as criminal offenses, are considered socially irrelevant. The present research was based on a bibliographic review, pertinent legislation and analysis of judicial decisions related to the theme. The study highlighted the importance of the principle of insignificance as an instrument to contain the punitive power of the State, avoiding the criminalization of conducts with low social impact and focusing the resources of the criminal justice system on more relevant cases. In the context of the action of the police authority, the applicability of the principle of insignificance gains relevance, since it is the responsibility of these bodies to carry out preliminary investigations and apply precautionary measures. The approach of insignificance by the police authority can avoid the initiation of unnecessary criminal proceedings, directing the efforts of the judiciary towards the repression of more serious conduct. The study pointed out that the application of the principle of insignificance by the police authority requires a careful and sensitive analysis of the particularities of each case. It is essential to consider factors such as the absence of relevant injury or danger, the minimal offensiveness of the conduct, the inexpressiveness of the legal injury and the absence of social disapproval. The results obtained indicate that the proper application of the principle of insignificance by the police authority contributes to a more efficient and fair performance, avoiding overloading the penal system and preserving the social function of Criminal Law. However, the importance of solid and up-to-date training for professionals in the area of public security is highlighted, as well as the adoption of objective and clear criteria in the analysis of cases. DOI:https://doi.org/10.56238/globalhealthprespesc-068